Examining the effect of oil price pass-through on the domestic prices: asymmetric versus symmetric adjustment modelling - Koh, Yan Chyi; Lim, Wei Hong; Sek, Siok Kun (Penerbit Universiti Kebangsaan Malaysia, 2020)
We study the effect of oil price pass-through on the domestic prices, namely on the consumer price index (CPI) and producer price index (PPI), based on the asymmetric adjustment modelling approach. The behaviour of domestic prices in response to oil price changes was examined by comparing two groups of economies, namely the oil-importing versus oil-exporting countries. The results show that although the oil price has a significant influence on the domestic price inflation in the short-run and in the long-run for most of the oil-importers and oil-exporters, it is not the main factor affecting CPI and PPI inflation. Moreover, oil price inflation seems to trigger a higher impact on PPI inflation than CPI inflation. The pass-through of oil prices on CPI inflation is low, especially in the oil-importing countries while the main determinant of CPI and PPI inflation is gross domestic product (GDP). The results are found to hold for both groups of countries.